2020
DOI: 10.1002/jev2.12005
|View full text |Cite
|
Sign up to set email alerts
|

Bisecting GlcNAc modification diminishes the pro‐metastatic functions of small extracellular vesicles from breast cancer cells

Abstract: Small extracellular vesicles (sEVs) are enriched in glycoconjugates and display specific glycosignatures. Aberrant expression of surface glycoconjugates is closely correlated with cancer progression and metastasis. The essential functions of glycoconjugates in sEVs are poorly understood. In this study, we observed significantly reduced levels of bisecting GlcNAc in breast cancer. Introduction of bisecting GlcNAc into breast cancer cells altered the bisecting GlcNAc status on sEVs, and sEVs with diverse bisecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…Notably, N-glycosylation in the I-like and membrane-proximal domains of integrin β1 is critical for integrin-mediated functions [14,23]. Integrin β1 is reported to regulate the migratory ability of recipient cells via sEVs [1,7]. We hypothesized that site-specific N-glycosylation could modulate behaviors of recipient cells via transfer of vesicular integrin β1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, N-glycosylation in the I-like and membrane-proximal domains of integrin β1 is critical for integrin-mediated functions [14,23]. Integrin β1 is reported to regulate the migratory ability of recipient cells via sEVs [1,7]. We hypothesized that site-specific N-glycosylation could modulate behaviors of recipient cells via transfer of vesicular integrin β1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that sEVs in soluble compounds from MDA-MB-231 cells enhance the migratory ability of MCF7 cells by addition of GW4869, an N-sMase2 inhibitor that blocks ceramide-mediated release of sEVs [1]. Integrin β1 was documented to be present on sEVs and transferred to recipient cells, resulting in enhanced cell migration [1,20], suggesting that integrin β1 might affect the cell migration and adhesion of recipient cells via sEVs. Given the important role of N-glycosylation in the I-like domain of integrin β1, we focused on the ∆4-6 mutant in the subsequent experiments.…”
Section: Effects Of β1 Mutants On Biological Function Of Sevsmentioning
confidence: 99%
See 3 more Smart Citations